2021
DOI: 10.1126/sciadv.abg2873
|View full text |Cite
|
Sign up to set email alerts
|

No ordinary proteins: Adsorption and molecular orientation of monoclonal antibodies

Abstract: The interaction of monoclonal antibodies (mAbs) with air/water interfaces plays a crucial role in their overall stability in solution. We aim to understand this behavior using pendant bubble measurements to track the dynamic tension reduction and x-ray reflectivity to obtain the electron density profiles (EDPs) at the surface. Native immunoglobulin G mAb is a rigid molecule with a flat, “Y” shape, and simulated EDPs are obtained by rotating a homology construct at the surface. Comparing simulations with experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 56 publications
3
54
0
Order By: Relevance
“…For all the mAb concentrations studied, the surface tension decreases and reaches a quasi-equilibrium value as molecules adsorb to the surface. At long times, the tension continues to decrease and does not achieve an equilibrium value, indicating irreversible adsorption of mAbs upon adsorption due to unfolding or slow rearrangements of the adsorbed mAbs. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For all the mAb concentrations studied, the surface tension decreases and reaches a quasi-equilibrium value as molecules adsorb to the surface. At long times, the tension continues to decrease and does not achieve an equilibrium value, indicating irreversible adsorption of mAbs upon adsorption due to unfolding or slow rearrangements of the adsorbed mAbs. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…This value is lower than the area per molecule for the maximum packing of the flat-on orientation (18,750 Å 2 ) but higher than that for the side-on (6875 Å 2 ) or end-on (8250 Å 2 ) orientation. Prior studies using homology modeling by our group have indicated that the adsorbed layer surface population could consist of a mixture of all three orientations (flat-on, side-on, and end-on) …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding to a strongly hydrophobic surface entails the risk of protein unfolding and exposition of hydrophobic domains, resulting in a partial denaturation, which is a typical phenomenon observed for passive adsorption of antibodies [ 41 , 42 ]. The reported degree of Abs denaturation may reach about 50%, which derives from protein conformational changes and random immobilization, hindering solvent accessibility of binding sites [ 43 ]. It is however worth underlining that in our case this effect is fully compensated for by the benefits resulting from the increased surface area.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the tendency to adsorb onto the interface (e.g., greater foaming ability) increases the level of denaturation. 31 In this aspect, the equilibrium surface tension of lactoferrin (or the surface activity of lactoferrin) is similar to iGg, 43 rhGH, 59 mAbs, 60 and lysozyme 61 (with an equilibrium surface tension of 20 µM ~ 55-60 mN/m). These are proteins known to degrade with exposure to the air-water interface through the aeration of the solution.…”
Section: Implications Of Stresses Incurred During Droplet Formation On Lactoferrin Conformationmentioning
confidence: 97%